Trust, Fairness, and Ethics in the Digital Age: A Systematic Literature Review on Their Impact on SME Performance - Bono Prambudi (ASIAN PUBLISHER, 2024)
This study aims to analyze the influence of the implementation of trust, fairness, and ethics on the performance of Micro, Small, and Medium Enterprises (MSMEs) in facing the challenges of digital transformation. Through a quantitative approach and cross-country comparative literature study, this study examines how moral and relational factors affect the sustainability and productivity of MSMEs. The results of this study are supported by global findings, including from Agarwal (2014) in India regarding the importance of trust in work relationships; Tlaiss et al. (2015) in Canada and Brown et al. (2015) in the UK regarding the role of fairness and organizational support in improving performance; and Abdullahi et al. (2016) in Nigeria which emphasizes ethics as the foundation of business. Other studies such as Engelbrecht et al. (2017) in South Africa and Afsar et al. (2018) in Pakistan show that fairness and ethics increase employee loyalty and performance. In the digital context, studies by Wong et al. (2020) in Hong Kong, Chamtitigul & Li (2021) in China, and Oh et al. (2022) in South Korea underlines the importance of digital ethics and trust in the modern business ecosystem. Research by Alpkan et al. (2020) in Turkey and Umar et al. (2024) in Nigeria confirms that organizational justice and ethical leadership can strengthen the competitiveness of MSMEs amidst digitalization. The findings of this study indicate that the synergy between trust, justice, and ethics is a crucial foundation in improving MSME performance, especially in facing digital disruption. Therefore, MSMEs need to internalize these values ​​in managerial practices in order to survive and develop sustainably.